EFETIVAÇÃO DAS DECISÕES DO SISTEMA INTERAMERICANO DE DIREITOS HUMANOS EM CASOS SENSÍVEIS: A RESPOSTA DO STF AOS CASOS GOMES LUND E BELO MONTE: EFFECTIVENESS OF THE DECISIONS OF THE INTER-AMERICAN SISTEM OF HUMAN RIGHTS IN SENSITIVE CASES: THE STF’S RESPONSE TO CASES GOMES LUND AND BELO MONTE (Revista Direitos Humanos e Democracia, 2021)
This work objective to explain how the STF seeks to justify non-compliance with the Inter-American Human Rights System decisions in sensitive cases, and to that end, the qualitative content analysis method is applied to inductively verify arguments used by the STF ministers that shape the behavior of the State and incorporate them into the respective categories. The results demonstrate that the Brazilian judiciary attaches greater importance to the issue of political-institutional power and governance, considering that in the Belo Monte case the arguments of decisions prioritize the country's energy development to the detriment of the affected populations and, in relation to the case Gomes Lund the declaration of constitutionality of the Amnesty Law that exempts the agents of the crimes committed during the dictatorship from criminal liability.